The synthesis, thermal and photophysical properties of phenoxycyclotriphosphazenyl-substituted cyclic and polymeric phosphazenes - Cosut, Buenyemin; Hacivelioglu, Ferda; Durmuş, Mahmut; Kilic, Adem; Yeşilot, Serkan (Pergamon-Elsevier Science Ltd, 2009)
An hydroxyl substituted hexa(phenoxy)cyclotriphosphazene (3) is reacted with hexachlorocyclotriphosphazene, N3P3Cl6, octachlorocyclotetraphosphazene, N4P4Cl8 and poly(dichlorophosphazene), (Cl2P=N)(n), to give cyclic compounds (4 and 5) and a polymeric compound (6). The newly synthesised compounds have been fully characterised by elemental analysis, MALDI-TOF mass spectrometry, gel permeation chromatography (6), FT-IR, H-1, C-13 and P-31 NMR spectroscopy. The thermal stability and fluorescence spectral properties of all these novel compounds have been investigated. It was found that the thermal stability and fluorescence spectral properties of cyclic compounds 4 and 5 are superior to those of compound 6. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclophosphazene; Polyphosphazene; P-31 NMR; Thermal stability; Fluorescence